In situ measurements of cemented paste backfilling in an operating stope at Lanfranchi Mine - Hasan, A.; Suazo, G.; Doherty, J.P.; Fourie, A.B. (Mine Fill 2014: Proceedings of the Eleventh International Symposium on Mining with Backfill, 2014)
This paper presents results from in-stope measurements of total stress and pore pressure during and after backfilling with cemented paste backfill (CPB). Measurements were taken at the Lanfranchi Nickel Mine, Western Australia, in collaboration with Panoramic Resources Ltd. The sensor installation procedure, which was developed to fit within a tight time production schedule, is described. Direct measurements of total stress, and pore pressure throughout filling and resting cycles at specific locations within the stope provide insight into the mechanical response of mine backfill during the filling and hydrating process, which is important for developing rational models to improve mine backfill management.